SPEECH ACTS IN THE WEDDING OF BATAK TOBA ETHNIC AT JANGGA TORUAN VILLAGE, KECAMATAN LUMBAN JULU KABUPATEN TOBA SAMOSIR - Linarti Manurung; Saiful Anwar Matondang; Muhammad Ali Pawiro (Universitas Islam Sumatera Utara, 2023)
The marriage of the Batak Toba community is closely related to the role of Dalihan Na Tolu, something that cannot be separated from Batak Toba customs because Dalihan Na Tolu is a symbol of the social system of the Batak Toba people, which has three pillars consisting of Hula-hula, Dongantubu, and Boru. The function of Dalihan Na Tolu, besides assisting the respective relatives, also plays a role in providing the materials for carrying out traditional Batak Toba weddings. The purpose of this research is to describe the implementation of speech acts in the wedding of the Batak Toba indigenous people and also to describe the types of speech acts in the Batak Toba wedding. In this case, the theory of speech acts is taken from Austin, which is then developed by Searle. The method used is a descriptive qualitative method supported by data analysis techniques based on the information given by the community leaders in the village of Janggatoruan, Kecamatam, Lumban, Julu, Kabupaten, and Toba Samosir. The findings of this study are of four speech acts in the wedding: 1) representative speech acts; 2) expressive speech acts; 3) directive speech acts; and 4) declarative speech acts.